The stage of change approach for implementing ergonomics advice – Translating research into practice. (March 2017) - Rothmore, Paul; Aylward, Paul; Oakman, Jodi; Tappin, David; Gray, Jodi; Karnon, Jonathan
Abstract: The Stage of Change (SOC) approach has been proposed as a method to improve the implementation of ergonomics advice. However, despite evidence for its efficacy there is little evidence to suggest it has been adopted by ergonomics consultants. This paper investigates barriers and facilitators to the implementation, monitoring and effectiveness of ergonomics advice and the adoption of the SOC approach in a series of focus groups and a subsequent survey of members of the Human Factors Societies of Australia and New Zealand. A proposed SOC assessment tool developed for use by ergonomics practitioners is presented. Findings from this study suggest the limited application of a SOC based approach to work-related musculoskeletal injury prevention by ergonomics practitioners is due to the absence of a suitable tool in the ergonomists' repertoire, the need for training in this approach, and their limited access to relevant research findings. The final translation of the SOC assessment tool into professional ergonomics practice will require accessible demonstration of its real-world usability to practitioners and the training of ergonomics practitioners in its application. Highlights: This paper investigates the barriers and facilitators to the use of the Stage of Change approach in ergonomics practice. These were studied among members of the Human Factors and Ergonomics Societies of Australia and New Zealand. A proposed stage of change assessment tool is presented. The limited use is due to the absence of a suitable tool, the need for training and limited access to research findings.